2018
DOI: 10.1038/s41598-018-21187-2
|View full text |Cite
|
Sign up to set email alerts
|

The drought-tolerant Solanum pennellii regulates leaf water loss and induces genes involved in amino acid and ethylene/jasmonate metabolism under dehydration

Abstract: Breeding for drought-tolerant crops is a pressing issue due to the increasing frequency and duration of droughts caused by climate change. Although important sources of variation for drought tolerance exist in wild relatives, the mechanisms and the key genes controlling tolerance in tomato are little known. The aim of this study is to determine the drought response of the tomato wild relative Solanum pennellii (Sp) compared with the cultivated tomato Solanum lycopersicum (Sl). The paper investigates the physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 75 publications
2
72
0
1
Order By: Relevance
“…The highly inbred tomato cultivar M82 has traditionally been used as a check variety in breeding programmes (Grandillo et al, 1999) and as a reference cultivar for scientific research, used in relation to the response to water stress as a drought-sensitive cultivar (Iovieno et al, 2016), in contrast with the drought-tolerant S. pennellii (Egea et al, 2018). The IL population has been used extensively for functional and physiological studies (Steinhauser et al, 2011;Chitwood et al, 2013;de Oliveira Silva et al, 2018), and the natural variation within the IL population provides an excellent platform to investigate the role of differences in epidermal features on performance under water stress.…”
Section: Variation Amongst the Ils And The Potential For Developing Dmentioning
confidence: 99%
“…The highly inbred tomato cultivar M82 has traditionally been used as a check variety in breeding programmes (Grandillo et al, 1999) and as a reference cultivar for scientific research, used in relation to the response to water stress as a drought-sensitive cultivar (Iovieno et al, 2016), in contrast with the drought-tolerant S. pennellii (Egea et al, 2018). The IL population has been used extensively for functional and physiological studies (Steinhauser et al, 2011;Chitwood et al, 2013;de Oliveira Silva et al, 2018), and the natural variation within the IL population provides an excellent platform to investigate the role of differences in epidermal features on performance under water stress.…”
Section: Variation Amongst the Ils And The Potential For Developing Dmentioning
confidence: 99%
“…The decrease in starch might have resulted from the starch degradation pathway that was elicited by water stress as also observed from transcriptomic analysis in tomatoes by Egea et al (Egea et al, 2018). In a wild relative of tomato, Lycopersicum pennellii upregulation of Fructose Insensitive 1 (FINS1) gene, which codes for a cytosolic fructose 1-6 bisphosphatase and down regulation of genes related to starch biosynthesis (ADG1) were also established under drought stress (Egea et al, 2018). This suggested that the tolerant tomato species prevents allocation of carbon towards starch synthesis and utilizes it for production of sugars.…”
Section: Effect Of Abiotic Stresses On Carbohydrate Concentration Andmentioning
confidence: 71%
“…To the contrary, starch levels remained comparatively low at the end of the day, hinting at a possibility that changes in sugar and starch levels may playa roleas important indicators for drought response associated with diurnal rhythms in rice (Kim et al, 2017). The decrease in starch might have resulted from the starch degradation pathway that was elicited by water stress as also observed from transcriptomic analysis in tomatoes by Egea et al (Egea et al, 2018). In a wild relative of tomato, Lycopersicum pennellii upregulation of Fructose Insensitive 1 (FINS1) gene, which codes for a cytosolic fructose 1-6 bisphosphatase and down regulation of genes related to starch biosynthesis (ADG1) were also established under drought stress (Egea et al, 2018).…”
Section: Effect Of Abiotic Stresses On Carbohydrate Concentration Andmentioning
confidence: 94%
“…In this regard breeding for drought-tolerant tomato varieties is an important and urgent task due to the increased frequency and duration of droughts caused by climatic change. There has been much research aiming to development of tolerant tomato varieties but the process is slow and difficult due to the complex and multigenic control of drought tolerance [11], [12]. The approaches to breeding drought-resistant included: 1. screening of available germplasm for drought tolerant/adapted varieties; 2. hybridization with wide species distinguished by enhance drought tolerance; 3. genetic transformation [13], [14].…”
Section: Introductionmentioning
confidence: 99%